TRAUMA, PELARIAN, DAN MARGINALITAS: STUDI WACANA KRITIS NORMAN FAIRCLOUGH ATAS LAGU DIARY DEPRESIKU LAST CHILD - Wahyudi, Teges; Shofiyuddin, Haris (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2025)
This article aims to analyze the song's lyrics using the critical discourse approach developed by Norman Fairclough. This analysis focuses on three main dimensions: text dimensions, discursive practices, and social practices. In the text dimension, the lyrics of this song use strong and emotional diction, such as "liquor" and "scratching the glass on my arm", which describe a form of destructive escape from trauma. In the dimension of discursive practice, this song aims to build social awareness and connect the subject's personal experiences with the audience, creating space for empathy towards those who experience similar problems. Socially, these lyrics also reflect the inequality in a social system that ignores the need for emotional support, so that individuals feel forced to seek self-destructive escape.